1992
DOI: 10.1161/01.res.70.3.566
|View full text |Cite
|
Sign up to set email alerts
|

Time course of changes in intracellular K+, Na+, and pH of subendocardial Purkinje cells during the first 24 hours after coronary occlusion.

Abstract: We investigated the basis for the alterations in the intracellular potassium and sodium activity occurring in subendocardial Purkinje fibers surviving in 24-hour infarcts by examining ion activities in these Purkinje fibers removed from infarcting hearts at earlier times. Specifically, we examined intracellular potassium activity, sodium activity, and pH at 1 and 3 hours after ligation of the left anterior descending coronary artery, and we correlated the changes in ion activity with changes in maximum diastol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…In the latter, fibers were removed from visibly infarcted myocardium with minimal or no mapping (4,6,13,14,16,17,19). In vivo and in vitro correlation studies showed that spontaneous VT originates in Purkinje tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the latter, fibers were removed from visibly infarcted myocardium with minimal or no mapping (4,6,13,14,16,17,19). In vivo and in vitro correlation studies showed that spontaneous VT originates in Purkinje tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In coronary sinus, mitral valve, and some atrial preparations, catecholamines may also produce TA (32). Ischemia serves as a typical model as well, because the acute process produces intracellular Ca 2ϩ (18) as well as Na ϩ (14) overload. The addition of catecholamines may also facilitate TA but is not required.…”
Section: Discussionmentioning
confidence: 99%
“…In acute ischemia, the elevated extracellular potassium is only one of the factors that depress the active membrane properties, and other changes in ionic composition and metabolic compounds are involved as well. [11][12][13][14][15] An important limitation of the present model is that we have deliberately reduced the ventricles to a 2-dimensional subepicardial substrate of VT. Cryoablation of the endocardial and midmyocardial layers of the left ventricle eliminated the possible participation of these structures in our studies. This is in contrast to the arrhythmogenic substrate after chronic myocardial infarction, which has a more complex 3D architecture.…”
Section: Limitations Of the Studymentioning
confidence: 99%
“…Fluorescent indicators have recently been developed to measure the intracellular free Ca 21 (41), Na 1 (17), and K 1 (22) concentrations. A remarkable amount of new information was gained by using fluorescent Ca 21 chelators. The impact of Na 1 and K 1 indicators is significantly less because of their limited specificity.…”
Section: Intracellular Potassium Determinationsmentioning
confidence: 99%